2021
DOI: 10.1037/aap0000218
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the connections between watching Asian American YouTubers, racial identity, and self-esteem.

Abstract: We explored the relationship between watching Asian American YouTubers and self-esteem among East and Southeast Asian Americans, specifically investigating 3 components of racial identity (i.e., in-group solidarity, satisfaction, and centrality) as mediators. Participants were 409 Asian Americans aged 18 to 34 years who stated that they watch Asian American YouTubers (i.e., users of YouTube who produce and often star in their own videos). Structural equation modeling was used to examine mediation paths from fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…One possible reason for this finding is that beauty-related YouTube videos can impact a viewer’s self-esteem both positively and negatively. This finding aligns with a previous study that suggested that YouTube videos can both hurt and help the viewer’s self-esteem based on their understanding and relatability to the beauty-related YouTube content creators [ 66 ]. However, another possibility is that YouTube users comment on their existing self-esteem levels when viewing YouTube content and may not be influenced by the videos themselves.…”
Section: Studysupporting
confidence: 92%
“…One possible reason for this finding is that beauty-related YouTube videos can impact a viewer’s self-esteem both positively and negatively. This finding aligns with a previous study that suggested that YouTube videos can both hurt and help the viewer’s self-esteem based on their understanding and relatability to the beauty-related YouTube content creators [ 66 ]. However, another possibility is that YouTube users comment on their existing self-esteem levels when viewing YouTube content and may not be influenced by the videos themselves.…”
Section: Studysupporting
confidence: 92%
“…For some AAM, however, shame fostered social isolation and deterred help-seeking. Fortunately, promising models of online support groups for AAM (Chang & Yeh, 2003) are available, as are social media and other virtual platforms through which to disseminate untold stories of AAM’s lived experiences (McCullough et al, 2021) while circumventing biased mainstream institutional structures.…”
Section: Discussionmentioning
confidence: 99%
“…Black emerging adults may engage with content, groups/forums, and social interactions that favorably represent their racial group in order to develop more positive racial identities. For instance, Asian American emerging adults who watched Asian American YouTubers more frequently were more satisfied with and felt more positively about their own racial identity (McCullough et al., 2021). It may be that, for those emerging adults for whom being Black is an important and positive part of their identity, using Twitter identity explorations entails selectively seeking out and connecting with other individual Black users.…”
Section: Discussionmentioning
confidence: 99%